Análisis de la Gestión de las Tecnologias de la Información (TI) Dentro del Plan Estrategico Empresarial del Grupo Intercom - Litardo, John Emmanuel Tobar; Campos, Germán Edwin Frías; Santistevan, Darío Xavier Romero; Alvarado, Mildred Kenia Barrientos (European Scientific Journal, ESJ, 2019)
This paper focuses on the need to integrate the processes under a strategic planning that considersthe management of Information Technologies (IT) as a relevant factor in the competitiveness of the INTERCOM group. Based on what has been proposed, we analyzed the perception of the members of the business group based on Information technology (IT) management. This is used for the integration of different operational processes which is both administrative and competitive. For the development of the study a methodology with a qualitative approach was used such that through nonexperimental research, the relevant factors could be described by contrasting the strategic perspectives of the Balanced Scorecard with IT resources. Therefore, the importance of IT management and the relationship with business strategy was determined. Also, a potential IT risk was identified in the learning perspective due to the lack of qualified personnel that contribute significantly to the innovation, development, and competitiveness of the business group. El presente estudio se centra en la necesidad de integrar los procesos bajo una planeación estratégica que considera la gestión de las TI como factor relevante en la competitividad del grupo INTERCOM. En función a lo planteado se propone analizar la percepción de los miembros del grupo empresarial basándose en la gestión de las tecnologías de la información (TI) para la integración de los diferentes procesos tanto operacionales como administrativos en función de la competitividad. Para el desarrollo del estudio se utilizó una metodología con un enfoque cualitativo que a través de la investigación no experimental, podría describir los factores relevantes contrastando las perspectivas estratégicas del Cuadro de Mando Integral con los recursos de las TI. De esta manera, se determinó la importancia de la gestión de las TI y la relación con la estrategia empresarial identificando un riesgo potencial de las TI en la perspectiva de aprendizaje por la falta de personal calificado que contribuye significativamente a la innovación, desarrollo y competitividad del grupo empresarial.